Gênese e desenvolvimento histórico-filosófico do conceito de Ideologia em Marx e Engels - Gonçalves, Nélio (2019)
This article aims to understand and explain, in general terms, the development process, historical-philosophical, of the concept of Ideology in Karl Marx (1818 - 1888) and Friedrich Engels (1820 - 1895) more precisely, from the work The German Ideology. We wish to understand what makes it a concept so dear to Marxism and modern philosophy, strong influence on the contemporary thought, evidencing its importance within the capitalist system. We want to understand how ideology is articulated and used in the construction of discourses from the dominant perspective, its function in obtaining political power and the maintenance of this system. However, to explain some causes, sone must go back to Greece and some of its principal philosophical representatives: Parmenides, Plato, Aristotle. This will be decisive to reveal the serious philosophical implications in the constitution of ideologies. We will try to understand that idealism transcendent of Plato, as well as the theory of the four causes of Aristotle, are two paths by which unfold processes which allowed the permanence of a system of hierarchization, domination through alienation through idealistic conceptions. Such conceptions are determinants of a mystified reality, whose real processes are hidden in function of certain perspective of the world stimulating an "inverted consciousness of this very reality," whose causes, according to Marx and Engels, emerge from the relations of material and spiritual production.